Synthesis and Characterization of Natural Pahae Zeolite–Durian Peel Activated Carbon as an Adsorbent for Phosphate Reduction in Laundry Wastewater - Susilawati; Fadhilah, Siti; Anggraini, Friska (Journal of Technomaterial Physics, 2025)
This study aims to synthesize and characterize composites based on Pahae Natural Zeolite and Durian Peel Activated Carbon as phosphate reducers in laundry wastewater. Zeolite was activated using 1 M NaCl solution, while activated carbon was prepared by carbonization at 500 °C for 2 hours. The Zeolite–Activated Carbon mixtures were prepared with compositions of 100%:0%, 95%:5%, 90%:10%, 85%:15%, 80%:20%, 75%:25%, and 0%:100%, pressed at 6 tons for 10 minutes, and sintered at 700 °C, 800 °C, and 900 °C for 4 hours. Characterization included physical properties (porosity, water absorption), mechanical properties (hardness), morphology (SEM), crystal structure (XRD), and elemental composition (XRF). The results showed that the optimum condition was achieved at a 75%:25% composition and 700 °C, with porosity of 59.67%, water absorption of 56.06%, and phosphate reduction efficiency of 80.86%. The highest hardness value was obtained at 100%:0% composition at 900 °C, reaching 784.14 MPa. Therefore, the Pahae Natural Zeolite–Durian Peel Activated Carbon composite demonstrates potential as an effective and environmentally friendly adsorbent for wastewater treatment.